CYLD deficiency promotes pancreatic cancer development by causing mitotic defects. Issue 6 (26th October 2018) - Xie, Songbo; Wu, Yuhan; Hao, Huijie; Li, Jingrui; Guo, Song; Xie, Wei; Li, Dengwen; Zhou, Jun; Gao, Jinmin; Liu, Min
Abstract: Successful treatment of pancreatic cancer, which has the highest mortality rate among all types of malignancies, has challenged oncologists for decades, and early detection would undoubtedly increase favorable patient outcomes. The identification of proteins involved in pancreatic cancer progression could lead to biomarkers for early detection of this disease. This study identifies one potential candidate, cylindromatosis (CYLD), a deubiquitinase and microtubule‐binding protein that plays a suppressive role in pancreatic cancer development. In pancreatic cancer samples, downregulation of CYLD expression resulted from a loss in the copy number of the CYLD gene; additionally, reduced expression of CYLD negatively correlated with the clinicopathological parameters. Further study demonstrated that CYLD deficiency promoted colony formation in vitro and pancreatic cancer growth in vivo. Mechanistic studies revealed that CYLD is essential for spindle orientation and properly oriented cell division; CYLD deficiency resulted in a substantial increase in chromosome missegregation. Taken together, these data indicate a critical role for CYLD in suppressing pancreatic tumorigenesis, implicating its potential as a biomarker for early detection of pancreatic cancer and a prognostic indicator of patient outcomes. Abstract : This study identifies one potential candidate, cylindromatosis (CYLD), a deubiquitinase and microtubule‐binding protein that plays a suppressive role in pancreatic cancer development, implicating its potential as a biomarker for early detection of pancreatic cancer and a prognostic indicator of patient outcomes.